Evaluation of the anthropogenic radionuclide concentrations in sediments and fauna collected in the Beaufort Sea and northern Alaska - Efurd, D. W.; Miller, G. G.; Rokop, D. J. (Los Alamos National Laboratory, 1997)
This study was performed to establish a quality controlled data set about the levels of radio nuclide activity in the environment and in selected biota in the U.S. Arctic. Sediment and biota samples were collected by the National Oceanic and Atmospheric Administration (NOAA), the National Biological Service, and the North Slope Borough`s Department of Wildlife Management to determine the impact of anthropogenic radionuclides in the Arctic. The results summarized in this report are derived from samples collected in northwest Alaska with emphasis on species harvested for subsistence in Barrow, Alaska. Samples were analyzed for the anthropogenic radionuclides sup 90Sr, sup 137Cs, sup 238Pu, sup 239Pu, sup 240Pu and sup 241Am. The naturally occurring radionuclides sup 40K, sup 212Pb and sup 214Pb were also measured. One goal of this study was to determine the amounts of anthropogenic radionuclides present in the Beaufort Sea. Sediment samples were isotopically fingerprinted to determine the sources of radio nuclide activities. Biota samples of subsistence and ecological value were analyzed to search for evidence of bio-accumulation of radionuclides and to determine the radiation exposures associated with subsistence living in northern Alaska. The anthropogenic radio nuclide content of sediments collected in the Beaufort Sea was predominantly the result of the deposition of global fallout. No other sources of anthropogenic radionuclides could be conclusively identified in the sediments. The anthropogenic radio nuclide concentrations in fish, birds and mammals were very low. Assuming that ingestion of food is an important pathway leading to human contact with radioactive contaminants and given the dietary patterns in coastal Arctic communities, it can be surmised that marine food chains are presently not significantly affected.